A 5‐Year Retrospective Analysis of Biologic and Prosthetic Complications Associated With Single‐Tooth Endosseous Dental Implants: Practical Applications. Issue 4 (16th April 2021) - Kaur, Maninder; Abou‐Arraj, Ramzi V.; Lin, Chee Paul; Geisinger, Maria L.; Geurs, Nicolaas C.
Abstract : Focused Clinical Question: What are the key considerations of the incidence and timing for single‐tooth implant complications, including early failure, biological complications, and prosthetic complications? Summary: Single‐tooth dental implants have been shown to have a high overall survival rate, but implant complications affect patient satisfaction and may lead to costly and/or time‐consuming repair and revision. Assessing the incidence and types of biologic and prosthetic complications and the timing of such complications is helpful so that the underlying causes can be addressed during the treatment planning process. Furthermore, identification of patient demographics, patient‐, implant‐, and site‐specific factors associated with such complications may allow for more comprehensive risk assessment during treatment planning. Conclusions: Overall, dental implants have a high survival rate. Identification of the incidence of both biologic and prosthetic complications and minimizing their impact in patients with dental implants is critical to overall implant success. Utilization of careful treatment planning and dental implant fixtures, surgical protocols, and prosthetic designs that reduce complication rates can improve patient acceptance and outcomes. Further research is necessary to fully assess complication rates and risk factors.